2019
DOI: 10.1096/fj.201802683r
|View full text |Cite
|
Sign up to set email alerts
|

Betaine attenuates pathology by stimulating lipid oxidation in liver and regulating phospholipid metabolism in brain of methionine‐choline–deficient rats

Abstract: Methyl‐donor deficiency is a risk factor for neurodegenerative diseases. Dietary deficiency of the methyldonors methionine and choline [methionine‐choline–deficient (MCD) diet] is a well‐established model of nonalcoholic steatohepatitis (NASH), yet brain metabolism has not been studied in this model. We hypothesized that supplemental betaine would protect both the liver and brain in this model and that any benefit to the brain would be due to improved liver metabolism because betaine is a methyl‐donor in liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 60 publications
2
7
0
2
Order By: Relevance
“…Earlier studies on animal models of NAFLD have shown that betaine reduces lipid peroxidation and nitrosative stress by increasing glutathione content and antioxidative enzymes activity (Kwon et al, 2009; Xu et al, 2015) in the liver, thus restoring the respiratory chain function in mitochondria (Wei et al, 2008). Based on present study results as well as on previous studies (Abu Ahmad et al, 2019; Pierantonelli & Svegliati-Baroni, 2019), we may assume that antioxidative effects of betaine can contribute to steatosis alleviation in NAFLD. Furthermore, a recent study from our laboratory has shown that betaine exerts anti-inflammatory and antiapoptotic effects and stimulates autophagy processes in mice liver with MCD diet-induced NAFLD (Veskovic et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Earlier studies on animal models of NAFLD have shown that betaine reduces lipid peroxidation and nitrosative stress by increasing glutathione content and antioxidative enzymes activity (Kwon et al, 2009; Xu et al, 2015) in the liver, thus restoring the respiratory chain function in mitochondria (Wei et al, 2008). Based on present study results as well as on previous studies (Abu Ahmad et al, 2019; Pierantonelli & Svegliati-Baroni, 2019), we may assume that antioxidative effects of betaine can contribute to steatosis alleviation in NAFLD. Furthermore, a recent study from our laboratory has shown that betaine exerts anti-inflammatory and antiapoptotic effects and stimulates autophagy processes in mice liver with MCD diet-induced NAFLD (Veskovic et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…However, this question could not be answered, since serum HCys was not normalized by the betaine-supplemented diet, but elevated compared to App NL–G–F control animals. Interestingly, it has also been reported previously that betaine did not lead to a decrease in HCys or even further increased levels ( Kunisawa et al, 2015 ; Ahmad et al, 2019 ). A reason for this might be reduced food intake by the mice due to a potential aversion against the betaine-containing chow and, as a consequence, even lower intake of dietary choline and additionally decreased methylation capacity.…”
Section: Discussionsupporting
confidence: 73%
“…Mice fed a high-sucrose diet also exhibit significant fat accumulation and increased lipogenic activity in the liver similar to what was seen in high-fat diet administration, which were attenuated with betaine treatment via upregulation of AMPK [ 160 ]. Betaine supplementation to mice with MAFLD induced by methionine- and choline-deficient diet alleviated steatosis, inflammation, apoptosis, and oxidative stress, normalized mitochondrial size and respiratory chain function, stimulated β-oxidation of fatty acids, increased the number of autophagosomes, and restored both glutathione content and antioxidant enzyme activities in livers [ 28 , 161 , 162 , 163 ].…”
Section: Disease Prevention By Betaine Administrationmentioning
confidence: 99%